Climate Change and Adaptation Strategies of Spanish Catalan Alpine Ski Resorts - David Sauri; Joan Carles Llurdés (Revue de Géographie Alpine)
Ski tourism in Catalonia has long been a fundamental socioeconomic asset for the Pyrenees region. However, in recent years some studies increasingly warn about the dubious future viability of most ski resorts as a result of climate change, and recommend the implementation of adaptation strategies for seasons in which snow maybe absent or insufficient. In this context, the article analyzes the evolution of the most common adaptation strategies to increasingly problematic ski seasons: on the one hand, the installation of snowmaking facilities and, on the other, the diversification of the main tourist product, skiing, towards other, snow-independent leisure activities. In Spanish Catalan resorts we observe that snowmaking is widespread but that, according to some scenarios, could not ensure the future viability of most resorts. The transformation of the ski resorts in mountain resorts represents in principle a more reliable adaptation measure although it has still to prove its potential on two critical questions: the impacts of climate change on new activities and the environmental consequences of the same activities.